Implikasi Pergeseran Sistem Politik terhadap Hukum dan Birokrasi di Indonesia - Suryo Gilang Romadlon (The Constitutional Court of the Republic of Indonesia, 2016)
Coalition can be the effective way to collect the power for struggle in the competitive politics. In Indonesia, after the reform era, the coalition system being the most popular system that granted by the constitution. Phrase ”coalition of political parties” in the article number 6A point (2) UUD 1945 shows us that the coalition system is the constitutional and the fix way. From all the historical story about the coalition of political parties in Indonesia, we can make a conclusion that the coalition system wich is exist in Indonesia is just coalition made by interest, not ideology. Coalition only to reach the “threshold”. Political parties only thinking about how to complete the mission to propose the candidate. Surely, That’s all the problem. We can see that the coalition system in Indonesia just make some paradox. For example, in presidential election 2014, in one hand we can see the batle between “KMP” and “KIH”, but in the other hand, we cand find a different situation in local politic competition. On 9 December 2015, The simultaneous regional election was completed held, and I saw that the battle between KMP and KIH wasn’t happened in that moment. Based on the fact from KPU, we can find in some region, the inconsistence coalition was built by the political parties which is member of KMP join with member of KIH. That condition shows us that the coalition system in Indonesia is just based on interest. There is no linear/consistence coalition between central and local, so automatically we can find a question, “where is the platform, vision and mission of political party in Indonesia? And How about the impact to the bureaucratic system between central and local government?. Finally, The Author is trying to answer the questions in this paper.